2009
DOI: 10.4005/jjfs.91.366
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Sap Flux Measurements in Moso Bamboo (Phyllostachys pubescens): Relationship between Water Absorption and Whole-tree Water Use Utilizing Granier Sensor Sap Flux Measurements.

Abstract: . J. Jpn. For. Soc. 91: 366 370. Although sap flux measurement is one of the most robust techniques for stand-scale transpiration estimates, its applicability to bamboo is unclear. Ultimately we aim to establish a method for sap flux-based stand-scale transpiration estimates in a bamboo forest. This study focused on establishing a method for individual-scale transpiration estimates. We conducted sap flux measurements using hand-made 1-cm length sensors, and water absorption measurements in cut-bamboo. The sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In the bamboo forest, canopy transpiration was measured using the sap-flow technique (Onozawa et al 2009b;Kume et al 2010;Komatsu et al 2010b). The value of E in the bamboo stand was compared with the canopy transpiration based on the sap-flow technique.…”
Section: Soil-water Budget Methodsmentioning
confidence: 99%
“…In the bamboo forest, canopy transpiration was measured using the sap-flow technique (Onozawa et al 2009b;Kume et al 2010;Komatsu et al 2010b). The value of E in the bamboo stand was compared with the canopy transpiration based on the sap-flow technique.…”
Section: Soil-water Budget Methodsmentioning
confidence: 99%
“…The eastern side of the forest faced a natural broadleaved forest, and the other sides faced coniferous plantation forests. The Moso bamboo forest at this site has invaded the surrounding forests (Onozawa et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…For several tree species, since it is impossible to measure the sapwood area of all trees in a stand, the relationship between stem diameter and sapwood area is determined to estimate the stand sapwood area (e.g., Wullschleger et al 2001;Kumagai et al 2005). On the other hand, the vascular bundles of bamboo species are widely distributed throughout the culm wall (Liese 1998;Onozawa et al 2009b), and thus the total cross-sectional area of the culm wall in the stand, Ac _stand , should be used as an alternative for A S_stand in Eq. 3.…”
Section: Implication For Stand Transpiration Estimatementioning
confidence: 99%
“…Onozawa et al (2009b) found that the sap flux density J S for P. pubescens can be measured with the Grainer sensor (Granier 1987). For several tree species, since it is impossible to measure the sapwood area of all trees in a stand, the relationship between stem diameter and sapwood area is determined to estimate the stand sapwood area (e.g., Wullschleger et al 2001;Kumagai et al 2005).…”
Section: Implication For Stand Transpiration Estimatementioning
confidence: 99%
See 1 more Smart Citation